A Cone Stacked on a Cone Within a Cone: A Technique for Reconstructing Proximal Third Tibial Shaft Fractures During Revision Total Knee Arthroplasty - Stefano Ghirardelli, MD; Peter Sculco, MD; Jeffrey O'Donnell, MD; Daniel Buchalter, MD; Elizabeth Gausden, MD; Brian Chalmers, MD; Thomas Sculco, MD (Arthroplasty Today)
Bone loss in revision total knee arthroplasty is an increasing challenge, especially as younger active patients undergo primary procedures. Treatment options for severe tibial bone loss include cement, allograft, metal augments, metaphyseal cones, sleeves, and megaprostheses. Novel combinations of these have enabled complex limb salvage without resorting to megaprostheses or amputation. This case report presents a technique utilizing three cones—configured in both cone-in-cone and cone-on-cone fashion—to bypass and stabilize a metadiaphyseal fracture during revision total knee arthroplasty. We outline the indications for selecting each construct and explain how to achieve axial and rotational stability in different bone zones using patient-specific cones. This approach provides an alternative to traditional reconstruction methods in complex cases with significant bone loss and periprosthetic fracture.